The Reform Movement in Algeria: Challenges and Difficulties - Ibn Badis as a Model - - Mokhtar , Mokhtar; Abdelhafidi, abdesalam (El Omda in Linguistics and Discourse Analysis, 2025)
preserving Algerian identity، confronting French cultural assimilation. His efforts focused on establishing schools to revive the Arabic language and instill Islamic values as an alternative to the French educational system. Despite the numerous challenges he faced، including the suppression of educational institutions by colonial authorities، Ben Badis continued his work by organizing cultural associations and magazines to raise national awareness.